ФОРМЫ ТРЕХКОМПОНЕНТНЫХ СВЕРХСКОПЛЕНИЙ ГАЛАКТИК - Панько, Е. А. (Одеські астрономічні публікації, 2011)
We analyzed the shapes of galaxy superclusters, contains only 3 galaxy clusters. The superclusters were found using PF Catalogue Galaxy Clusters and Groups covering 5000 square degrees as input data. We applied Friend-of-Friend method and found 111 galaxy superclusters including 62 three-member ones. We showed the real superclusters are elongated structures. In best fit ellipse approximation the typical value of minor axis less than 0.5 of major axis; 30% of the galaxy clusters triplets have minor axis less than 0.8 of major axis. The Kolmogorov-Smirnov test confirmed this property is not random.